2009
DOI: 10.1088/0031-8949/79/04/045502
|View full text |Cite
|
Sign up to set email alerts
|

Parallel propagation of ion solitons in magnetic flux tubes

Abstract: We introduce features of propagating ion-acoustic solitons parallel to the magnetic field lines of magnetic flux tubes. A nonlinear model is used. The model considers both isothermal Boltzmann electrons and finite-temperature warm ions. The electrons are composed of two components, background electrons and energetic ones. A soliton-potential equation is obtained for a generalized oblique magnetic field. With a parameterized numerical study, the effect of several parameters on soliton waves is examined. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Numerous satellites have measured these non-wave solitons and confirmed the simultaneity between spikelet electric field structures and energetic ion populations (see e.g. Carlqvist and Boström 1970, Cattell et al 1991, Dusenbery et al 1988, Mottez 2001, and references in Ma and Hirose 2009, Temerin et al 1982, Vago et al 1992.…”
Section: Introductionmentioning
confidence: 84%
“…Numerous satellites have measured these non-wave solitons and confirmed the simultaneity between spikelet electric field structures and energetic ion populations (see e.g. Carlqvist and Boström 1970, Cattell et al 1991, Dusenbery et al 1988, Mottez 2001, and references in Ma and Hirose 2009, Temerin et al 1982, Vago et al 1992.…”
Section: Introductionmentioning
confidence: 84%
“…It deserves to mention again that these three shapes of IA E x structures (i.e., sinusoidal, sawtooth, and spiky/bipolar) are well-known in satellite observations. They were first reported by S3-3 satellite in late 1970s (Temerin et al, 1979) and have thereafter been detected in various regions in geospace by numerous satellites (see a detailed review in Ma and Hirose, 2009a).…”
Section: In the Absence Of Electron Inertia: Parallel-propagating Ia mentioning
confidence: 98%
“…This fact was highlighted in the introduction to Ma and Hirose (2009a) where the authors gave a thorough discussion of prior literature in this field, and showed that there are often differences in nomenclature used by different authors. Table 1.…”
Section: A Preliminary Simulation To Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group-2 presents simple waves in the lower two panels, θ and δ, characterized by the wave packets of hybrid sinusoidal and saw-tooth waveforms [16].…”
Section: Inadequacy Of the Argumentmentioning
confidence: 99%